(E)-3-(2,4-Dimethoxyphenyl)-1-(3,4,5-trimethoxyphenyl)prop-2-en-1-one - Jianzhang Wu; Junyan Qiu; Xiaokai Wu; Shulin Yang; Yonggen Liu (Acta Crystallographica Section E, 2012)
In the title chalcone derivative, C20H22O6, the dihedral angle between the mean planes of the benzene rings is 15.77 (6)°. The H atoms of the central C=C double bond are in a trans configuration. There are a number of C—H...O interactions and a C—H...π interaction present in the crystal structure.